Exploring Age-Based Disparities: A Study of Age and Generational Trends Towards Professional Development Programs in Ahmedabad - Arjama Patra; Pooja Vataliya; Chandni J. Vidani (MultiTech Publisher, 2024)
This primary research study delves into the nuances of age-based disparities regarding professional development programs in Ahmedabad, India. Recognizing the increasing diversity within the workforce, the research employs a mixed-methods approach to comprehensively explore how different age groups perceive and engage with these programs. Specifically targeting Generation Z, Millennials, and older generations, the study aims to assess awareness, attitudes, and participation levels in professional development initiatives. The research aims to give a greater knowledge of the intersections between age, generational patterns, and desires about professional progress by combining surveys that are quantitative and interviews of a qualitative nature. The ultimate goal is to offer valuable insights beneficial to employers, educators, and policymakers, helping them tailor strategies to effectively engage and empower individuals across diverse age groups. This study is important because it adds to the larger conversation on labour management and the development of talent. By shedding light on the unique considerations necessary for addressing age-based disparities in professional development initiatives, the findings serve as a valuable resource for organizations and institutions striving to foster continuous professional growth among their employees.